TMIC-18. IMPACT OF HFE MUTATION ON VIABILITY IN MACROPHAGES EXPOSED TO GLIOBLASTOMA EXOSOMES. (5th November 2018) - Nesterova, Darya; Mrowczynski, Oliver; Slagle-Webb, Becky; Madhankumar, Achuthamangalam; Zacharia, Brad; Nixon, Anne; Connor, James
Abstract: In Glioblastoma (GBM), the tumor microenvironment is critical to cancer development and progression. Glioblastoma Extracellular Vesicles (GBM-EVs) have been shown to promote a tumor-supporting phenotype in macrophages, leading to surrounding immunosuppression and enhanced tumor growth. Microglia and macrophages contribute to iron homeostasis, essential for cellular energy production in rapidly dividing cells. The HFE mutation is associated with altered cellular iron homeostasis. It is the most common autosomal recessive polymorphism found in Caucasians and may be linked to worse patient prognosis in GBM. Our lab showed that HFE mutation confers phenotypic differences between HFE and wild-type (WT) macrophages, with HFE macrophages displaying increased migration and phagocytosis. How these phenotypic differences may present in response to GBM exosomes has not yet been explored. Primary macrophage cultures isolated from bone marrow of WT and HFE mutant knock-in mice were exposed to exosomes from different patient-derived cancer stem cells. Significant differences in macrophage viability 24 hours after exosome exposure were observed in response to GBM exosomes (p= 0.001). When exposed to GBM exosomes, WT macrophage viability consistently decreased while the viability of macrophages with the HFE mutation increased. There was no significant difference between the two genotype macrophage groups when exposed to U87 exosomes, supporting that the stem cells are modulating macrophage phenotype. These data suggest that genotypic differences in iron handling pay a critical role in macrophage response to GBM exosomes and may be responsible for differences seen in disease severity in patients with HFE mutations.